2022
DOI: 10.2196/33768
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Telemedicine in a Rural US Cancer Center Amid the COVID-19 Pandemic: Qualitative Study

Abstract: Background The COVID-19 pandemic necessitated a rapid shift to telemedicine to minimize patient and provider exposure risks. While telemedicine has been used in a variety of primary and specialty care settings for many years, it has been slow to be adopted in oncology care. Health care provider and administrator perspectives on factors affecting telemedicine use in oncology settings are not well understood, and the conditions associated with the COVID-19 pandemic offered the opportunity to study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Our finding that high self-rated health of patients is an influencing patient characteristic for suitability of video visits echoes the finding that patients with less complex, more straightforward clinical needs are more suitable candidates for video visits than those with complex, high-risk diseases [ 10 , 29 ]. Similar findings were identified in an oncological study wherein telemedicine was received favorably for low-acuity cancer care [ 16 ]. In contrast to findings that video visits appear to be more appropriate when the clinician knows the patient beforehand and when it is a follow-up visit [ 10 ], we found that the reason for the visit did not have any influence on whether patients rated the video visit positively.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our finding that high self-rated health of patients is an influencing patient characteristic for suitability of video visits echoes the finding that patients with less complex, more straightforward clinical needs are more suitable candidates for video visits than those with complex, high-risk diseases [ 10 , 29 ]. Similar findings were identified in an oncological study wherein telemedicine was received favorably for low-acuity cancer care [ 16 ]. In contrast to findings that video visits appear to be more appropriate when the clinician knows the patient beforehand and when it is a follow-up visit [ 10 ], we found that the reason for the visit did not have any influence on whether patients rated the video visit positively.…”
Section: Discussionsupporting
confidence: 85%
“…The 13-item survey by Hanna et al [7] is designed according to the principles of survey development for telemedicine to evaluate patients' experiences with video visits in pain clinics [26]. This survey was translated into Dutch, and 1 item was removed, as it was already covered by the PEM survey (Multimedia Appendix 1, items [16][17][18][19][20][21][22][23][24][25][26][27]. In total, 4 items were rephrased based on the advice of the patient communication experts.…”
Section: Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…This way of providing care offers several advantages, including saving travel time and costs for both patients and their companions and the efficient use of health care resources, such as outpatient clinic space and support [12][13][14]. As we move into the post-COVID-19 era, video visits are expected to persist as a routine practice, but large-scale use has seemed to stagnate, presumably owing to a lack of guidance, vision, and attention to patients' needs, as observed in the United States [15,16]. The use and implementation of video visits are expected to be most successful when tailored to the needs of patients, clinicians, and health care organizations [17,18].…”
Section: Introductionmentioning
confidence: 99%